Column [5] aryl solid adsorption material for high-selectivity adsorption of carbon dioxide as well as preparation and application of column [5] aryl solid adsorption material
By grafting N,N-dimethyldiguanidine onto a bromine alkylation column [5] aromatic hydrocarbon and loading it on porous silica gel, column [5] aromatic hydrocarbon-based solid adsorption material with multi-stage porous structure was prepared, and the solution was solved In the prior art, the problem of insufficient selectivity and adsorption amount of carbon dioxide adsorbent has achieved an efficient and stable carbon dioxide capture effect.
Patent Information
- Application Number
- CN202411765628.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing porous column aromatic hydrocarbon solid amine carbon dioxide adsorbents have poor performance in selective adsorption of carbon dioxide gas and have low adsorption amount, making it difficult to meet the demand for efficient capture of carbon dioxide.
By grafting N,N-dimethyldiguanidine onto a bromine alkylated column [5] aromatic hydrocarbon and loading it on porous silica gel, a column [5] aromatic hydrocarbon-based solid adsorption material with a multi-stage porous structure was prepared, and the column [5] aromatic hydrocarbon-based solid adsorption material was prepared using Its ultramicroporous, mesoporous and macroporous structures improve the adsorption capacity and selectivity of carbon dioxide.
This adsorption material significantly improves the dynamic saturation adsorption amount and separation selectivity of carbon dioxide, and can maintain efficient adsorption performance in multiple cycles and reuses. It is suitable for efficient capture of carbon dioxide, especially in closed spaces or coalbed methane and other environments.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a novel solid adsorbent material with high efficiency in capturing carbon dioxide, and in particular to a method for preparing a columnar [5] aromatic hydrocarbon-based solid adsorbent material with high selectivity in absorbing carbon dioxide, so as to improve the efficiency of capturing carbon dioxide. The present invention belongs to the technical field of composite materials and the field of capture, conversion and utilization of resources and energy. Background Art
[0002] For a long time, carbon dioxide has been the largest contributor to global warming greenhouse gases due to its excessive emissions, and capturing, storing and utilizing carbon dioxide is considered one of the most important methods. Using amine-based materials to adsorb and separate carbon dioxide from carbon dioxide-rich gas streams has become a feasible technology. Among the many capture technologies, solid adsorption is considered to be one of the most effective ways to remove carbon dioxide in the short term and achieve emission reduction effects due to its high selectivity, low energy consumption, large adsorption capacity, and easy regeneration and reuse.
[0003] CN202311030582.3 discloses a method for preparing a porous column aromatic solid amine carbon dioxide adsorbent, which further reacts with ethylenediamine by halogenation through column aromatic bonded amination porous silicon to obtain a porous column aromatic solid amine carbon dioxide adsorbent, which has high carbon dioxide gas adsorption capacity and strong stability. However, it also has the disadvantages of less than ideal performance of selective adsorption of carbon dioxide gas and low adsorption capacity. Therefore, it is urgent to develop a new solid adsorption material with efficient capture of carbon dioxide. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a column [5] aromatic hydrocarbon-based solid adsorbent material with high selectivity for adsorbing carbon dioxide, so as to improve the efficiency of capturing carbon dioxide.
[0005] Another object of the present invention is to provide a column for highly selectively adsorbing carbon dioxide [5] and to use the aromatic hydrocarbon-based solid adsorbent material in selectively adsorbing and separating carbon dioxide from mixed gases.
[0006] 1. Preparation of Column [5] Aromatic Hydrocarbon-Based Solid Adsorption Materials The carbon dioxide column [5] aromatic hydrocarbon solid adsorption material of the present invention is prepared by using N, N-dimethyl biguanidine and bromoalkylated column [5] aromatic hydrocarbon as reaction precursors and triethylamine as catalyst. In anhydrous acetone, N, N-dimethyl biguanidine is grafted onto bromoalkylated column [5] aromatic hydrocarbon and loaded onto porous silica gel. The specific preparation process is as follows: dissolving bromoalkylated column [5] aromatic hydrocarbon in anhydrous acetone, then adding N, N-dimethyl biguanidine and triethylamine, reacting at 75-80°C for 20-24h; then adding porous silica gel and refluxing for 20-24h; then distilling off the solvent under reduced pressure at 55-60°C, washing the obtained solid with ethanol, drying it, and roasting it at 180-200°C in a nitrogen atmosphere for 1-2 hours, and passing it through a 20-40 mesh sieve to obtain the N, N-dimethyl biguanidine modified bromoalkylated column [5] aromatic hydrocarbon solid adsorption material.
[0007] In the above preparation process, the mass ratio of the bromoalkylation column to N,N-dimethylbiguanidine is 1:1~1:1.5; the mass ratio of the bromoalkylation column to triethylamine is 10:1~20:1; and the mass ratio of the bromoalkylation column to porous silica gel is 1:2~1:4.
[0008] 2. Structural characterization of column[5] aromatic-based solid adsorption materials The following experiments are carried out using the column [5] aromatic hydrocarbon-based solid adsorption material for selective adsorption of carbon dioxide prepared in Example 1 as an example, and the morphology of the material was characterized by scanning electron microscopy.
[0009] Figure 1 This is a scanning electron microscope image of the column [5] aromatic hydrocarbon-based solid adsorption material. Figure 1 It can be seen that the column [5] aromatic hydrocarbon-based solid adsorption material presents a morphology of silicon spheres bonded and stacked. The material has a rough surface and an obvious stacking pore structure. The formation of these stacking pores will be more conducive to the high-capacity adsorption of carbon dioxide.
[0010] Figure 2 This is the infrared characterization spectrum of the column [5] aromatic hydrocarbon-based solid adsorbent material. In the figure, the broad band at 3550~3300 wavenumbers is attributed to the N-H and Si-OH stretching vibration peaks of N, N-dimethyl biguanidine and porous silica gel, and the characteristic peaks at 2936 and 2867 wavenumbers are the symmetric and asymmetric stretching vibrations corresponding to the C-H bond in the alkyl chain. The characteristic peak at 1658 wavenumber is the −C=N double bond stretching vibration peak of N, N-dimethyl biguanidine, while the characteristic peak at 1615 wavenumber is attributed to the −NH bending vibration peak of N, N-dimethyl biguanidine in the column [5] aromatic hydrocarbon multi-level porous material for selective adsorption of carbon dioxide, and the characteristic peak at 1502 wavenumber is attributed to the N-H deformation vibration peak of aliphatic secondary amine. The infrared spectrum results show that the column [5] aromatic hydrocarbon-based solid adsorbent material for selective adsorption of carbon dioxide was successfully prepared.
[0011] Figure 3This is the nitrogen adsorption-desorption isotherm of column [5] aromatic hydrocarbon-based solid adsorbent material, where the inset shows the pore size distribution. Figure 3 The results showed that the column [5] aromatic solid adsorbent material has a typical IV type N2 desorption curve and its surface area is 238m 2 / g, pore volume and pore diameter are 0.4 cm 3 / g and 7.4nm, these data all indicate that the column [5] aromatic-based solid adsorption material has an obvious mesoporous pore structure.
[0012] Figure 4 Mercury intrusion porosimetry analysis of aromatic hydrocarbon-based solid adsorbent materials. Figure 4 The pore volume of the material is 1.8 cm 3 / g, pore size of 71nm, porosity of 69%, confirming the existence of macroporous structure, which provides favorable conditions for CO2 adsorption. The mesopores come from porous silica gel, while the formation of macropores may be the accumulation of porous silica gel during the polymer granulation process.
[0013] The nitrogen adsorption-desorption isotherm and mercury intrusion porosity analysis test confirmed that the multi-level porous material of the column [5] aromatic hydrocarbon-based solid adsorption material simultaneously has mesoporous and macroporous structures, and the column [5] aromatic hydrocarbon body contains ultra-microporous cavities. Therefore, the column [5] aromatic hydrocarbon-based solid adsorption material prepared by the present invention is a multi-level porous material, which has a good dynamic saturated adsorption capacity of carbon dioxide.
[0014] 3. Analysis of carbon adsorption performance of column [5] aromatic hydrocarbon-based solid adsorbent materials 1. Effect of adsorbent dosage on CO2 adsorption performance The temperature was set at 40 °C and the gas flow rate was set at 20 mL / min to investigate the effect of adsorbent dosage on CO2 adsorption capacity. Figure 5 Column [5] shows the effect of the amount of aromatic hydrocarbon-based solid adsorption material on the saturated adsorption capacity of CO2, where the inset shows the dynamic saturated adsorption capacity of CO2. Figure 5 The results show that when the adsorbent dosage increases from 0.2 g to 0.8 g, the breakthrough time of the CO2 dynamic adsorption process becomes shorter and the CO2 saturated adsorption capacity decreases. It can be seen that a certain amount of adsorbent has an enhancing effect on the adsorption capacity of CO2, and the adsorption mode is preferred in the CO2 dynamic adsorption process. Once the adsorbent is filled too much, the CO2 diffusion resistance increases, reducing its contact time with the active amine of the internal adsorbent, which will lead to a decrease in the saturated CO2 adsorption capacity.
[0015] 2. Effect of gas flow rate on CO2 adsorption performance Gas flow rate is an important factor affecting the capture capacity of adsorbent materials. At 30℃, 0.2g of adsorbent was selected to investigate the effect of gas flow rate on the dynamic adsorption performance of CO2. Figure 6The figure shows the effect of air flow rate on the saturated adsorption of CO2, and the illustration shows the dynamic saturated adsorption of CO2. Figure 6 It can be seen that as the gas flow rate increases from 10 mL / min to 50 mL / min, the breakthrough time of the CO2 dynamic adsorption process becomes shorter. When the gas flow rate is 20 mL / min, the dynamic saturated adsorption capacity of the adsorbent reaches a maximum value of 8 mmol / g, and then shows a downward trend.
[0016] 3. Effect of temperature on CO2 adsorption performance At a gas flow rate of 20 mL / min, 0.2 g of adsorbent was selected to investigate the effect of 30-60 ℃ on the dynamic adsorption performance of CO2. Figure 7 The effect of temperature on the saturated adsorption of CO2, where the inset is the dynamic saturated adsorption of CO2. The results show that as the temperature increases, the saturated adsorption of CO2 increases. When the temperature is 40°C, the saturated adsorption of CO2 by the adsorbent reaches 9.7 mmol / g. This is because the diffusion resistance of CO2 decreases with increasing temperature, and the structure of the multi-level porous material of the adsorbent stretches, exposing more active sites and improving the CO2 capture capacity. When the temperature is further increased, the dynamic adsorption process of CO2 prioritizes the desorption mode, resulting in a decrease in the CO2 adsorption capacity.
[0017] 4. Single component CO2 adsorption and desorption isotherm analysis The single-component CO2 adsorption and desorption isotherms of the adsorbent were investigated at 298 K. Figure 8 The single-component CO2 adsorption and desorption isotherms show that the CO2 adsorption amount increases sharply with the increase of relative pressure, and the difference at 298 K is 24 cm 3 / g, indicating that the adsorbent has good CO2 adsorption performance.
[0018] 5. Comparative analysis of CO2 / CH4 adsorption performance In order to evaluate the actual separation performance of the adsorbent, the CO2 / CH4 dynamic adsorption selectivity was investigated at a gas flow rate of 20 mL / min and a temperature of 40 °C. Fig. 9 This is an evaluation of the performance of the adsorbent in the selective separation of CO2 / CH4, where the illustration shows the dynamic saturated adsorption of CO2. It can be seen that the dynamic saturated adsorption of CO2 and CH4 by the adsorbent is 9.3mmol / g and 0.7mmol / g respectively, which has a high dynamic adsorption separation selectivity. During the entire dynamic adsorption process, the breakthrough time of CO2 is longer than that of CH4, indicating that the adsorption capacity of CO2 is stronger, indicating that the adsorbent has good separation potential for CO2 / CH4.
[0019] 6. Comparative analysis of CO2 / N2 adsorption performance The dynamic adsorption separation of CO2 / N2 was compared at a gas flow rate of 20 mL / min and a temperature of 40°C. Fig.10 This is an evaluation of the performance of the adsorbent for selective separation of CO2 / N2, where the illustration shows the dynamic saturated adsorption of CO2. It can be seen that the dynamic saturated adsorption of CO2 and N2 by the adsorbent is 9.5mmol / g and 0.4mmol / g, respectively, with high dynamic adsorption separation selectivity. During the entire adsorption process, the breakthrough time of CO2 is longer than that of N2, indicating that the adsorption capacity for CO2 is stronger, indicating that the adsorbent has good separation potential for CO2 / N2.
[0020] 7. CO2 cycle adsorption and desorption analysis In order to further explore the practical industrial application prospects and value of the adsorbent, a CO2 cyclic regeneration dynamic adsorption evaluation was carried out. A 5 vol% binary CO2 / Ar mixed gas was used as the analyte. CO2 was adsorbed at 40 °C, and then a desorption cycle experiment was carried out at a temperature of 110 °C with pure Ar as the carrier gas and a gas flow rate of 20 mL / min. Fig.11 It is the CO2 adsorption performance of the adsorbent during desorption cycle. It can be seen that after 15 consecutive repetitions of the adsorption and desorption process, the saturated adsorption capacity of the adsorbent for CO2 can still be maintained at 9 mmol / g, indicating that the adsorbent has good cyclic regeneration performance.
[0021] In summary, the present invention uses a "one-pot method" to graft N,N-dimethylbiguanidine to bromoalkylated column [5] aromatics and loads it onto porous silica gel to obtain a column [5] aromatics-based solid adsorption material. The adsorption material simultaneously contains ultra-microporous cavities of column [5] aromatics, mesopores of porous silica gel, and macroporous structures formed by porous silica gel granulation, which significantly promotes the adsorption performance of CO2. At the same time, due to the introduction of N,N-dimethylbiguanidine, more amine active sites exist inside the adsorbent, further improving the adsorption performance of the adsorbent for CO2. When the adsorption material is used to separate CO2 / CH4 and CO2 / N2 mixed atmospheres, the adsorption performance for CO2 is better than that for CH4 and N2, and has a higher separation selectivity for CO2 / CH4 and CO2 / N2. In addition, after 15 adsorption and desorption cycles, the saturated adsorption capacity of CO2 can still reach 9 mmol / g, which proves that the adsorption material has good stability and cyclic regeneration performance. It is a new type of solid amine adsorption material that is expected to achieve a large saturated adsorption capacity for CO2. It can be widely used in the efficient capture of carbon dioxide in closed spaces or coalbed methane, combustible ice and other environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the column [5] aromatic hydrocarbon-based solid adsorption material of the present invention.
[0023] Figure 2This is the infrared spectrum of the aromatic hydrocarbon-based solid adsorption material of column [5] of the present invention.
[0024] Figure 3 This is the N2 adsorption-desorption isotherm of the aromatic-based solid adsorbent material of this column [5].
[0025] Figure 4 Mercury intrusion porosimetry analysis of aromatic hydrocarbon-based solid adsorbent materials for column [5].
[0026] Figure 5 This is the effect of adsorbent dosage on the amount of carbon dioxide adsorbed.
[0027] Figure 6 The effect of gas flow rate on the amount of carbon dioxide adsorption.
[0028] Figure 7 The effect of temperature on the amount of carbon dioxide adsorption.
[0029] Figure 8 The adsorption and desorption isotherms of single component CO2 on aromatic hydrocarbon-based solid adsorbent material at 298 K.
[0030] Fig. 9 Selective adsorption of carbon dioxide / methane by column [5] aromatic hydrocarbon-based solid adsorbent material.
[0031] Fig.10 Selective adsorption of carbon dioxide / nitrogen by column [5] aromatic hydrocarbon-based solid adsorbent material.
[0032] Fig.11 To evaluate the regeneration performance of column[5] aromatic-based solid adsorbent material for dynamic cyclic adsorption of carbon dioxide.
[0033] Fig.12 The NMR of the bromoalkylation column [5] aromatic prepared in Example 1 of the present invention 1 H NMR spectrum.
[0034] Fig.13 The NMR of the bromoalkylated column [5] aromatic prepared in the embodiment of the present invention 13 C NMR spectrum. DETAILED DESCRIPTION
[0035] The preparation and performance of the aromatic hydrocarbon-based solid adsorption material of the column [5] of the present invention are further described below through specific examples.
[0036] Example 1 Preparation of bromoalkylated column [5] aromatics: At room temperature in a nitrogen atmosphere, take 10 mmol of 1, 1-dibromophenylene diethyl ether and dissolve it in 50 mL of anhydrous dichloromethane solvent, add 50 mmol of paraformaldehyde as a polymerization agent and 10 mmol of boron trifluoride ether as a catalyst, stir for 5.0 hours to obtain a green solution; then remove the solvent by vacuum distillation, and purify the obtained solid by column chromatography with a petroleum ether / dichloromethane mixture with a volume ratio of 2:1 to 1:1 to obtain bromoalkylated column [5] aromatics. Nuclear magnetic resonance of bromoalkylated column [5] aromatics 1 The H NMR spectrum is shown in Figure 12. The characteristic peak at 6.91 ppm corresponds to the hydrogen atom on the benzene ring, the characteristic peak at 4.25 ppm corresponds to the methylene hydrogen atom on the alkyl chain adjacent to oxygen, the characteristic peak at 3.85 ppm corresponds to the chemical shift value of the benzene ring bridged methylene peak, and the characteristic peak at 3.64 ppm corresponds to the hydrogen atom on the alkyl chain carbon atom adjacent to bromine. 1 H NMR spectrum showed the successful synthesis of bromoalkylated column [5] aromatic hydrocarbons. The corresponding spectral data were: (400MHz, CDCl3, rt), δ(ppm): 6.90 (s, 10H), 4.22 (t, 20H), 3.84 (s, 10H), 3.63 (t, 20H).
[0037] NMR of bromoalkylated column [5] aromatic hydrocarbons 13 C NMR spectrum Fig.13 The data showed that the characteristic peaks of carbon atoms were 149.68, 129.11, 116.13, 68.97, 30.72, 29.75 and 29.46, which once again confirmed the successful preparation of aromatics by bromoalkylation column [5].
[0038] Preparation of column [5] aromatic hydrocarbon-based solid adsorption material: 1.5 g of bromoalkylated column [5] aromatic hydrocarbon was dissolved in 80 mL of anhydrous acetone solvent, followed by addition of 1.5 g of N, N-dimethylbiguanidine and 0.1 g of triethylamine, and the mixture was reacted at 80 °C for 24 h, and then 4.5 g of porous silica gel was added and refluxed for 24 h; after the reaction was completed, the solvent was distilled off under reduced pressure at 60 °C, and the obtained solid was washed twice with 25 mL of ethanol, dried at 55 °C for 12 h, calcined at 200 °C for 1 h, and then filtered through a 20-mesh sieve to obtain the column [5] aromatic hydrocarbon-based solid adsorption material. The adsorption material has a high adsorption capacity for pure CO2, which can reach 9.7 mmol / g. When used to separate CO2 / CH4 and CO2 / N2 mixed atmospheres, the adsorbent has better adsorption performance for CO2 than CH4 and N2, with dynamic saturated adsorption capacities of (9.3 mmol / g and 0.7 mmol / g) and (9.5 mmol / g and 0.4 mmol / g), respectively. 2 / CH4 and CO2 / N2 have high separation selectivity.
[0039] Example 2 Preparation of bromoalkylation column [5] aromatic hydrocarbons: same as Example 1.
[0040] Preparation of column [5] aromatic hydrocarbon-based solid adsorption material: 1.6 g of bromoalkylated column [5] aromatic hydrocarbon was dissolved in 80 mL of anhydrous acetone solvent, followed by addition of 1.6 g of N, N-dimethylbiguanidine and 0.2 g of triethylamine, and the mixture was reacted at 75°C for 20 h, followed by addition of 4.0 g of porous silica gel and refluxed for 24 h; after the reaction was completed, the solvent was removed by vacuum distillation at 55°C, and the obtained solid was washed twice with 20 mL of ethanol, dried at 55°C for 10 h, calcined at 180°C for 2 h, and then filtered through a 40-mesh sieve to obtain the column [5] aromatic hydrocarbon-based solid adsorption material. The adsorption material has a high adsorption capacity for pure CO2, which can reach 9.3 mmol / g. When used to separate CO2 / CH4 and CO2 / N2 mixed atmospheres, the adsorbent has better adsorption performance for CO2 than CH4 and N2, with dynamic saturated adsorption capacities of (9.1 mmol / g and 0.8 mmol / g) and (9.2 mmol / g and 0.5 mmol / g), respectively. 2 / CH4 and CO2 / N2 have high separation selectivity.
[0041] Example 3 Preparation of bromoalkylation column [5] aromatics: same as in Example 1; Preparation of column [5] aromatic hydrocarbon-based solid adsorption material: 2.0 g of bromoalkylated column [5] aromatic hydrocarbon was dissolved in 100 mL of anhydrous acetone solvent, followed by addition of 2.0 g of N, N-dimethylbiguanidine and 0.5 g of triethylamine, and the mixture was reacted at 80°C for 24 h, and finally 5.0 g of porous silica gel was added and refluxed for 24 h; after the reaction was completed, the solvent was removed by vacuum distillation at 60°C, and the obtained solid was washed twice with 30 mL of ethanol, dried at 60°C for 12 h, calcined at 200°C for 1 h, and then filtered through a 40-mesh sieve to obtain the column [5] aromatic hydrocarbon-based solid adsorption material. The adsorption material has a high adsorption capacity for pure CO2, which can reach 9.2 mmol / g. When used to separate CO2 / CH4 and CO2 / N2 mixed atmospheres, the adsorbent has better adsorption performance for CO2 than CH4 and N2, with dynamic saturated adsorption capacities of (9.0 mmol / g and 0.8 mmol / g) and (9.1 mmol / g and 0.4 mmol / g), respectively. 2 / CH4 and CO2 / N2 have high separation selectivity.
Claims
1. A column[5]arene-based solid adsorption material for highly selective carbon dioxide adsorption is prepared by using N,N-dimethylbiguanidine and bromoalkylated column[5]arene as reaction precursors and triethylamine as catalyst. In anhydrous acetone, N,N-dimethylbiguanidine is grafted onto bromoalkylated column[5]arene and then loaded onto porous silica gel.
2. The method for preparing a column [5] aromatic hydrocarbon-based solid adsorbent material for highly selective carbon dioxide adsorption as claimed in claim 1, characterized in that: The bromoalkylation column [5] aromatic hydrocarbon is dissolved in anhydrous acetone, and then N,N-dimethylbiguanidine and triethylamine are added, and the reaction is carried out at 75-80°C for 20-24 hours; porous silica gel is then added and refluxed for 20-24 hours; the solvent is then distilled off under reduced pressure at 55-60°C, the obtained solid is washed with ethanol, dried, and then calcined at 180-200°C in a nitrogen atmosphere for 1-2 hours, and passed through a 20-40 mesh sieve to obtain N,N-dimethylbiguanidine modified bromoalkylation column [5] aromatic hydrocarbon-based solid adsorption material.
3. The method for preparing a column [5] aromatic hydrocarbon-based solid adsorbent material for highly selective carbon dioxide adsorption as claimed in claim 2, characterized in that: The mass ratio of aromatic hydrocarbon to N,N-dimethylbiguanidine in the bromoalkylation column [5] is 1:1~1:1.
5.
4. The method for preparing a column [5] aromatic hydrocarbon-based solid adsorbent material for highly selective carbon dioxide adsorption as claimed in claim 2, characterized in that: The mass ratio of aromatic hydrocarbon to triethylamine in the bromoalkylation column [5] is 10:1~20:
1.
5. The method for preparing a column [5] aromatic hydrocarbon-based solid adsorbent material for highly selective carbon dioxide adsorption as claimed in claim 2, characterized in that: In the bromoalkylation column [5], the mass ratio of aromatic hydrocarbon to porous silica gel is 1:2~1:
4.
6. Use of the column [5] for highly selective carbon dioxide adsorption as claimed in claim 1 in adsorbing carbon dioxide.
7. Use of the aromatic hydrocarbon-based solid adsorbent column [5] for highly selective carbon dioxide adsorption as claimed in claim 1 in selective adsorption and separation of carbon dioxide / methane mixed gases.
8. Use of the highly selective carbon dioxide adsorption column [5] prepared by the method of claim 1 in selective adsorption and separation of carbon dioxide / nitrogen mixed gases.
Citation Information
Patent Citations
Preparation and application of porous pillararene solid amine carbon dioxide adsorbent
CN116983959A
Cited By
Method for preparing porous silica gel carrier with high specific surface area by using water-soluble column [5] arene as pore-foaming agent and application of porous silica gel carrier
CN120437951A